Classifying and Mapping Periurban Areas of Rapidly Growing Medium-Sized Sub-Saharan African Cities: A Multi-Method Approach Applied to Tamale, Ghana - Karg, Hanna; Hologa, Rafael; Schlesinger, Johannes; Drescher, Axel; Kranjac-Berisavljevic, Gordana; Glaser, Ruediger (Land, 2019)
Periurban areas of growing cities in developing countries have been conceptualised as highly dynamic landscapes characterised by a mixture of socioeconomic structures, land uses and functions. While the body of conceptual literature on periurban areas has significantly increased over the past two decades, methods for operationalising these multi-dimensional concepts are rather limited. Yet, information about the location and areal extent of periurban areas is needed for integrated planning in the urban-rural interface. This article presents the results of a study aiming at classifying and mapping periurban areas along the urban-rural gradient of Tamale, a medium-sized city in Ghana. The study used a quantitative, multi-dimensional methodology involving the following as core elements: (1) a relative measure of how urban a place and its people are in terms of services, infrastructure and livelihoods (urbanicity index); (2) the diversity of households regarding their livelihoods and access to urban services; and (3) land use dynamics. Therefore, data from a household survey, as well as land use and other secondary geospatial data were collected and analysed at different spatial scales. The findings suggested that the periurban space consists of two main zones. Inner periurban areas are driven by urban expansion and the conversion of non-urban into urban land use is most visible here. These areas exhibit higher levels of socioeconomic diversity, compared to both rural and urban areas. Outer periurban areas are less dynamic in terms of land use change and exhibit lower building densities, and compared with rural areas, hold stronger links to the city related to the movement of people and goods. The spatial analysis revealed that periurban areas develop mainly along major transport corridors across administrative divisions, as well as in the form of periurban islands in the rural zone. This study set out to extend existing methodologies to map urban and periurban development in medium-sized cities in sub-Saharan Africa, useful for urban and regional planning beyond administrative boundaries.
CRIS-Team WoS Importer:2019-04-30

Das subsaharische Afrika: Entwicklungsdynamiken, Herausforderungen, Lösungsversuche - Krüger, Fred; Drescher, Axel; Louis, Norman; Titz, Alexandra (Geographische Rundschau, 2019)
In recent years, the pace and multiplicity of development dynamics in Sub-Saharan Africa has increased such that new explanatory approaches are needed to assess the spatial, economic and social transformation and propose adequate solutions to tackle poverty and vulnerability. Demographic scenarios indicate that Sub-Saharan societies will have to face a wide range of challenges in the coming decades. European development policies, Chinese economic intervention, or a new African urbanism serve as examples to highlight the diverse transformation that is currently affecting everyday livelihoods in Sub-Saharan Africa.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Human Development Index (HDI); Globaler Süden; fragmentierende Entwicklung; HDI; Human Development Index

Der Chilwa-See in Malawi: Seine ökologischen Probleme und deren soziale Auswirkungen - Chiotha, Sosten; Likongwe, Patrick; Drescher, Axel (Geographische Rundschau, 2019)
CRIS-Team Scopus Importer:2019-12-10

Global urbanization and food production in direct competition for land: Leverage places to mitigate impacts on SDG2 and on the Earth System - Barthel, Stephan; Isendahl, Christian; Vis, Benjamin N.; Drescher, Axel; Evans, Daniel L.; van Timmeren, Arjan (Anthropocene Review, 2019)
Global urbanization and food production are in direct competition for land. This paper carries out a critical review of how displacing crop production from urban and peri-urban land to other areas – because of issues related to soil quality – will demand a substantially larger proportion of the Earth’s terrestrial land surface than the surface area lost to urban encroachment. Such relationships may trigger further distancing effects and unfair social-ecological teleconnections. It risks also setting in motion amplifying effects within the Earth System. In combination, such multiple stressors set the scene for food riots in cities of the Global South. Our review identifies viable leverage points on which to act in order to navigate urban expansion away from fertile croplands. We first elaborate on the political complexities in declaring urban and peri-urban lands with fertile soils as one global commons. We find that the combination of an advisory global policy aligned with regional policies enabling robust common properties rights for bottom-up actors and movements in urban and peri-urban agriculture (UPA) as multi-level leverage places to intervene. To substantiate the ability of aligning global advisory policy with regional planning, we review both past and contemporary examples where empowering local social-ecological UPA practices and circular economies have had a stimulating effect on urban resilience and helped preserve, restore, and maintain urban lands with healthy soils.
CRIS-Team Scopus Importer:2019-07-09
Keywords: cropland; economic globalization; food security; Global South; global sustainability; human resilience; social-ecological teleconnection; soil health; urban and peri-urban agriculture; urbanization

Infrastrukturentwicklung und das Recht auf Stadt: Das Beispiel Daressalaam - Munishi, Emmanuel; Louis, Norman; Drescher, Axel; Krüger, Fred (Geographische Rundschau, 2019)
Im Kontext der urbanen Transformation im subsaharischen Afrika finden Möglichkeiten der Ordnung und Steuerung von Stadtentwicklung zwar zunehmende Beachtung. Fragen zur aktiven Mitgestaltung von Stadt durch ihre Bewohnerschaft bleiben aber meist noch unberücksichtigt. Das Projekt AfriCity am Institut für Geographie der Friedrich-Alexander-Universität Erlangen-Nürnberg untersucht die Wechselbeziehungen zwischen Umweltveränderungen, Ressourcennutzung und Recht-auf-Stadt-Prozessen in afrikanischen Städten südlich der Sahara. In der tansanischen Küstenmetropole Daressalaam ist eine Gerechtigkeitsperspektive für aktuelle Prozesse des städtischen Umbruchs relevant, da die jüngsten Transformationsprojekte dort weitreichende Auswirkungen z. B. auf städtische Straßenverkäufer hatten.<br
CRIS-Team Scopus Importer:2019-12-10
Keywords: Ostafrika; Tansania; Umsiedlung

Land tenure, food security, gender and urbanization in Northern Ghana - Nchanji, Eileen Bogweh; Chagomoka, Takemore; Bellwood-Howard, Imogen; Drescher, Axel; Schareika, Nikolaus; Schlesinger, Johannes (Land Use Policy, 2023)
Links between land tenure and food and nutritional insecurity are receiving increased attention. Nevertheless, urban and periurban dwellers face challenges in accessing land to produce food for subsistence and sale. An ethnographic study and food and nutrition insecurity survey were conducted between October 2013 and November 2014 in Tamale, Northern Region of Ghana, to explore the dynamic and recursive links between land access, food access and the ability to maintain resources to meet long-term needs. Results showed that infrastructural development and agriculture compete for land. The shortage of land for agricultural purposes was pronounced in urban areas (20%) than in periurban areas (1.3%) and rural areas (0%). Food insecure households were more likely to name a lack of land than anything else as the primary reason for their inability to grow crops (Fisher's exact probability = 0.040). Urban and periurban dwellers cope with the constraints posed in the communal tenure system by using strategies such as urban–periurban-rural migrant farming and buffer zone cultivation. The role of women in providing nutritious soups is especially important, and they use various mechanisms to circumvent their lack of access to land and provide food for the household. Political, economic and cultural elements thus interact to constitute the link between land and food.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Food and nutritional insecurity; Gender; Land tenure; Northern Ghana; Urban and periurban agriculture

Small-Town Agricultural Markets in Northern Ghana and Their Connection to Rural and Urban Transformation - Karg, Hanna; Bellwood-Howard, Imogen; Akoto-Danso, Edmund K.; Schlesinger, Johannes; Chagomoka, Takemore; Drescher, Axel (European Journal of Development Research, 2019)
Markets are critical in connecting small towns with agricultural activities in their rural hinterland. This paper presents data from north-eastern Ghana on grain marketing and trade flows, combined with data on expansion of built and transport infrastructure in five linked towns of a periodic market system. Rurally sourced goods flow through historically established small-town and regional markets to national and international markets. Simultaneously, infrastructure and service provision develops in those small towns. These trends are linked by recursive, reinforcing processes of increasing consumption, agricultural commercialisation and economic diversification. Historical structures, such as periodic markets, and the nature of the commodities involved are central to this linkage and interact with policy: the commodities concerned have been promoted in northern Ghana in preceding decades, and contribute to small-town market development by integrating smoothly into existing local systems. Historical continuity is therefore central to the role that small towns play in rural-urban transformation.
CRIS-Team WoS Importer:2019-03-20

Urbanisation reshapes gendered engagement in land-based livelihood activities in mid-sized African towns - Shackleton, C. M.; Drescher, Axel; Schlesinger, J. (World Development, 2020)
Most sub-Saharan African countries are experiencing accelerating rates of urban migration, which bring with it many opportunities and challenges for migrating households, urban planners, governments and local and national economies. At the household level urbanisation may drive changes in the allocation of household labour and consequently social and economic relations. Yet how these are manifest in land-based livelihood strategies of arable cropping, livestock husbandry and the collection of wild products in urban settings has rarely been considered. Here we examine the changing participation rates in land-based livelihood activities by male- and female-headed households along the rural–urban continua of six sub-Saharan African secondary towns. To capture the gendered changes in land-based livelihood strategies along the urban–rural continuum, 1156 randomly selected households were sampled along transects radiating out from the urban through the periurban to rural surrounds. Participation in different land-based livelihood strategies was recorded by means of a questionnaire. We show that engagement in one or more land-based livelihood activities is widespread (92% of all households), even amongst urban households (82%). We also show that there are marked changes in gendered participation for many land-based activities along the urbanisation gradient, with a general narrowing of differences in participation rates between male- and female-headed households with increasing urbanisation. These results indicate that land-based activities are components of not only rural livelihoods in Africa, but are also practiced by most urban households too, and that urbanisation reshapes some of the gendered dimensions of roles more typical of rural contexts.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Gender; Land; Livelihoods; Livestock; Urban agriculture; Wild resources (NTFPs)